Does the New Urbanization Influence Air Quality in China? - Wu, Yan; Cui, Zhixiang; Hu, Cong (Frontiers in Environmental Science, 2021)
Previous studies have empirically investigated the influence of China’s urbanization on atmosphere pollution, the findings in the literature are however controversial and inconclusive across regions, data, and methodologies. This study uses the city-level panel data, 113 key cities of environment protection from the Ministry of Ecology and Environment, covering most of the provinces in China for the period 2013–2017 to investigate the different impacts of the new urbanization pilot policy on air quality and related air pollutants including six major pollutant sources, which are PM2.5, PM10, SO2, CO, NO2, and O3. The study finds that, first, based on the difference-in-difference (DID) method, the new urbanization on average tends to improve the air quality in the pilot cities. Second, based on the quantile DID method, the new urbanization tends to improve the air quality in the lower air quality quantiles (0.1–0.6); however, it has no significant impact in the higher air quality quantiles (0.7–0.9). Third, the impacts of the new urbanization on the air quality vary among different energy-related air pollutants. The new urbanization pilot policy tends to restrain SO2, PM10, and PM2.5, increase CO and O3 and has no impact on NO2. The results indicate that China should pay more attention to promote green consumption and new energy applications and increase urban construction efficiency to further reducing air pollutions in the new urbanization process.